The Quality of Lecturer-Student Interaction as Predictors of Academic Achievement and Percieved Learning with Emotional Engagement as Mediator - Maya Fitria; Koentjoro Koentjoro; Wenty Marina Minza (UIN Sunan Kalijaga, 2022)
This study aimed to examine the fitness of a model that proposes the relationship between the quality of student-teacher interaction as predictors of academic achievement and perceived learning with emotional engagement as a mediator. Lecture-student interactions as the exogenous variable were measured with the Lecturer-student Interaction (LSI) questionnaire that contains four aspects: autonomy support, emotional support, academic support, and the framework used to measure the quality of lecturer-student interaction. The emotional involvements of students during lectures as the endogenous variable are the emotions (pleasure, boredom, despair, anger, hope, anxiety) that are often expressed in the lecture process. Emotional engagement is considered as the mediator variable. Perceived learning as the dependent variable is related to the ability of lecturers to arouse students' curiosity about the lecture material. The second dependent variable is academic achievement which is determined by the cumulative index report (GPA) from the previous semester. 270 students from many universities in Indonesia filled out the questionnaire. The conceptual model proposed in this study is incompatible with empirical data in the field. In the first model, lecturer-student interaction influences perceived learning mediated by emotional engagement because lecturer-student interaction will only significantly influence perceived learning through emotional engagement (full mediation). Directly and through mediation of emotional involvement, the influence of lecturer-student interaction variables is not significant on academic achievement. In the modified model, lecturer-student interaction influences perceived learning with emotional engagement and also significantly influences perceived learning without emotional involvement variables (partial mediation). The dynamics of the lecturer-student interaction relationship, emotional engagement, and academic achievement in this modified model remain the same as the first model. Abstrak. Penelitian ini bertujuan untuk menguji kesesuaian model yang mengusulkan hubungan antara kualitas interaksi siswa-guru sebagai prediktor prestasi akademik dan pembelajaran yang dirasakan dengan keterlibatan emosional sebagai mediator. Interaksi dosen-mahasiswa sebagai variabel eksogen diukur dengan kuesioner Interaksi Dosen-Mahasiswa (LSI) yang memuat empat aspek: dukungan otonomi, dukungan emosional, dukungan akademik, dan kerangka yang digunakan untuk mengukur kualitas interaksi dosen-mahasiswa. Keterlibatan emosional mahasiswa selama perkuliahan sebagai variabel endogen adalah emosi (senang, bosan, putus asa, marah, harap, cemas) yang sering diungkapkan dalam proses perkuliahan. Keterlibatan emosional dianggap sebagai variabel mediator. Persepsi pembelajaran sebagai variabel terikat berkaitan dengan kemampuan dosen membangkitkan rasa ingin tahu mahasiswa terhadap materi perkuliahan. Variabel terikat kedua adalah prestasi akademik yang ditentukan oleh Indeks Prestasi Kumulatif (IPK) semester sebelumnya. 270 mahasiswa dari berbagai universitas di Indonesia mengisi kuesioner. Model konseptual yang diajukan dalam penelitian ini tidak sesuai dengan data empiris di lapangan. Pada model pertama, interaksi dosen-mahasiswa mempengaruhi persepsi pembelajaran yang dimediasi oleh emotional engagement karena interaksi dosen-mahasiswa hanya akan berpengaruh signifikan terhadap persepsi pembelajaran melalui emotional engagement (full mediation). Secara langsung dan melalui mediasi keterlibatan emosional, pengaruh variabel interaksi dosen-mahasiswa tidak signifikan terhadap prestasi belajar. Pada model yang dimodifikasi, interaksi dosen-mahasiswa mempengaruhi pembelajaran yang dirasakan dengan keterlibatan emosional dan juga secara signifikan mempengaruhi variabel pembelajaran yang dirasakan tanpa keterlibatan emosional (mediasi parsial). Dinamika hubungan interaksi dosen-mahasiswa, emosional engagement, dan prestasi akademik pada model modifikasi ini tetap sama dengan model pertama.